Pemberdayaan Masyarakat Untuk Peningkatan Gizi Dan Sanitasi Di Kelurahan Sungai Pisang Kota Padang - Frima Elda; Randy Novirsa; Edita Elda; Kamal Kasra; Yessy Markolinda; Fadilla Azmi; Rezi Fatrima Surya; Adelia Delviana; Mardhatillah Marzuki; Azzahra Diva (BULETIN ILMIAH NAGARI MEMBANGUN, 2025)
Sungai Pisang, located in the Bungus Teluk Kabung District, is a coastal area with approximately 2,116 residents, most of whom earn their livelihood as fishermen. The community faces interrelated nutritional and sanitation problems, primarily due to limited waste-management facilities. Household waste and fish-processing residues are commonly burned or buried, resulting in environmental pollution and increasing the risk of infectious diseases. These conditions negatively affect the community’s nutritional status, particularly among vulnerable groups such as children under five and pregnant women. This community service program aims to strengthen community capacity in improving nutrition and sanitation through a participatory empowerment approach. The activities were carried out through preparation, socialization, and intervention. These included official meetings with local authorities, health education sessions for housewives, mothers of young children, and community health volunteers, as well as a Focus Group Discussion (FGD) to develop applicable waste-management solutions. The results showed an increase in community knowledge regarding balanced nutrition and family health. In addition, residents agreed to initiate organic-waste composting and reduce the use of single-use plastics. This program integrates nutrition interventions with environmentally based sanitation improvements, emphasizing that nutritional enhancement cannot be separated from local ecological conditions. Collaboration among local government, health workers, and the community is essential to creating a sustainable healthy environment that supports comprehensive improvements in nutritional status.